2023
DOI: 10.3233/jad-221189
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Choline Alphoscerate on Adult-Onset Cognitive Dysfunctions: A Systematic Review and Meta-Analysis

Abstract: Background: Choline alphoscerate (alpha glyceryl phosphorylcholine, α-GPC) is a choline-containing phospholipid used as a medicine or nutraceutical to improve cognitive function impairment occurring in neurological conditions including adult-onset dementia disorders. Despite its 1985 marketing authorization, there are still discrepancies between countries regarding its approval as a prescription medicine and discussions about its effectiveness. Objective: This study aimed to evaluate the efficacy of the α-GPC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 41 publications
0
12
0
2
Order By: Relevance
“…It has also been reported in a previous study that choline alphoscerate might play a role in acute cerebrovascular diseases by antagonizing the biochemical-functional deficiency of the cholinergic system in cases of ischemia-induced damage [13]. In fact, it has a beneficial effect on patients with neurodegenerative diseases such as Alzheimer's disease (AD), and the study reported that it significantly improved cognitive function in patients with mild to moderate conditions of AD [45]. As neuroinflammation plays an important role in Alzheimer's disease, this may be explained by this compound's potential anti-inflammatory properties [46].…”
Section: Discussionmentioning
confidence: 81%
“…It has also been reported in a previous study that choline alphoscerate might play a role in acute cerebrovascular diseases by antagonizing the biochemical-functional deficiency of the cholinergic system in cases of ischemia-induced damage [13]. In fact, it has a beneficial effect on patients with neurodegenerative diseases such as Alzheimer's disease (AD), and the study reported that it significantly improved cognitive function in patients with mild to moderate conditions of AD [45]. As neuroinflammation plays an important role in Alzheimer's disease, this may be explained by this compound's potential anti-inflammatory properties [46].…”
Section: Discussionmentioning
confidence: 81%
“…Our study investigates the potential of choline alphoscerate (α-GPC) in the evolving scenario of AD therapeutics, which is often characterized by treatments with limited disease-modifying properties ( Sheikh et al, 2023 ). Among choline precursors, α-GPC stands out as the most effective in enhancing in vivo Ach release ( Traini et al, 2013 ) and has been suggested as a potential neuroprotective agent for various pathological conditions associated with inflammatory phenomena ( Choi et al, 2020 ; Sagaro and Amenta, 2023 ; Sagaro et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cholinergic precursors have been among the initial therapeutic strategies attempting to counteract cholinergic impairment and to relieve cognitive decline occurring in dementia disorders. Among these, choline alphoscerate, also known as alpha-glyceryl-phosphoryl-choline (α-GPC), is considered one of the most suitable sources of choline ( Parnetti et al, 2001 ; Traini et al, 2013 ; Sagaro et al, 2023 ). Despite its presence in the pharmaceutical market since 1987, α-GPC experienced a decline in interest following the introduction of cholinesterase inhibitors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While α-GPC is found as an ingredient in dietary supplements in the U.S. and is a recently approved ingredient by Health Canada’s Food Directorate for use in supplemented foods [ 32 ], it is considered a novel food in the EU since it was not consumed to a significant degree as a food before 15 May 1997, therefore requiring a pre-market authorization [ 33 ]. Moreover, discrepancies in the use of this substance between countries have been reported since it is considered a prescription drug in some EU countries [ 34 ], such as in Italy where it is sold under the brand name Delacit.…”
Section: Introductionmentioning
confidence: 99%